The role of glial–neuronal metabolic cooperation in modulating progression of multiple sclerosis and neuropathic pain. (11th January 2019) - Robinson, Rachel R; Dietz, Alina K; Maroof, Asif M.; Asmis, Reto; Forsthuber, Thomas G
While the etiology of multiple sclerosis (MS) remains unclear, research from the clinic and preclinical models identified the essential role of inflammation and demyelination in the pathogenesis of MS. Current treatments focused on anti-inflammatory processes are effective against acute episodes and relapsing-remitting MS, but patients still move on to develop secondary progressive MS. MS progression is associated with activation of microglia and astrocytes, and importantly, metabolic dysfunction leading to neuronal death. Neuronal death also contributes to chronic neuropathic pain. Metabolic support of neurons by glia may play central roles in preventing progression of MS and chronic neuropathic pain. Here, we review mechanisms of metabolic cooperation between glia and neurons and outline future perspectives exploring metabolic support of neurons by glia.